Association between osteoarthritis and the incidence of Parkinson's disease in the United Kingdom. (2021) - Jacob, Louis; Smith, Lee; Koyanagi, Ai; Schnitzler, Alexis; Il Shin, Jae; Kostev, Karel
Abstract: Background: Little is known on the potential relationship between osteoarthritis and Parkinson's disease. Objective: Therefore, the objective of this retrospective cohort study was to analyze the association between osteoarthritis and the incidence of Parkinson's disease in patients followed up for up to 10 years in general practices in the United Kingdom. Methods: This study included patients diagnosed for the first time with osteoarthritis in one of 256 general practices in the United Kingdom between 2000 and 2016 (index date). Patients without osteoarthritis were matched (1:1) to those with osteoarthritis using propensity scores based on sex, age and index year. In individuals without osteoarthritis, index date corresponded to a randomly selected visit date. The outcome of this study was the 10-year cumulative incidence of Parkinson's disease in patients with and without osteoarthritis. Cox regression analyses were adjusted for common comorbidities. Results: This study included 260, 224 patients (62.0% women; mean [SD] age 66.4 [12.7] years). The 10-year cumulative incidence of Parkinson's disease was 1.2% in patients with osteoarthritis and 0.6% in their counterparts without osteoarthritis (log-rank p-value < 0.001). The adjusted Cox regression model further showed a positive and significant association between osteoarthritis and the incidence of Parkinson's disease (HR = 1.82, 95% CI: 1.63–2.02). Similar results were obtained in all sex and age subgroups. Conclusions: In this retrospective cohort study conducted in the United Kingdom, there was a positive association between osteoarthritis and the incidence of Parkinson's disease. More research is warranted to confirm or refute these findings in other settings and countries.